HUBUNGAN POSTUR KERJA, REPETISI DAN TEKANAN PANAS DENGAN KELUHAN MUSCULOSKELETAL DISORDER PADA TUBUH BAGIAN ATAS (Studi Kasus pada Pekerja Pabrik Kue Jipang Bagian Pembentukan di Kecamatan Ambarawa, Kabupaten Semarang Jawa Tengah) - Muhammad Viki; Daru Lestantyo; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Workers of Jipang Ambarawa Cake Factory form japan cake by hand. Work posture and hand repetition when forming a japan cake can cause complaints in joints, ligaments and tendons that lead to muscle pain complaints. Heat pressure due to extreme temperatures can accelerate the occurrence of muscle complaints. The purpose of this study was to analyze the relationship of posture, repetition and heat pressure with MSDs complaints on the upper body. This study uses cross sectional study which is a form of observational study and is analytic descriptive. The population of the research is all the workers of Ambarawa Jipang Cake Factory in the forming section which amounted to 35 people with the sampling method. The instrument of this study is a questionnaire (to collect data on the characteristics of respondents and complaints MSDs), video recording (to see the work posture and the number of reps), ordinary arc (to measure the upper body angle with job posture picture). The results showed there were 91.40% of samples had MSDs complaints on the wrist. Statistical analysis using Rank Spearman test to see the relationship of heat pressure with MSDs and Chi-Square Test to see the relationship between work posture and repetition with MSDs complaints. The test results showed there was a correlation between the repetition variable on the wrist (p = 0.049). There was no correlation between posture of work with MSDs complaints on upper neck (p = 0,441), shoulder (p = 0,992), upper arm (p = 0,416), forearm (p = 0,552) and wrist (p = 0,529). There was also no correlation between heat stress with MSDs complaints on the upper neck (p = 0.528), shoulders (p = 0.904), upper arm (p = 0.487), forearm (p = 0.380) and wrist (p = 0.429) . It is recommended for workers to stretch on the sidelines of doing work. For the owner of JIpang Cake Factory to redesign the work out layout.